Social Justice: School Administrative Staff Perceptions of Strengths, Challenges, and Training Needs in Section 504-Only Services - Rodriguez, Dora D.; Menchaca, Velma D.; Padilla, George (Journal of Leadership, Accountability and Ethics, 2021)
The unfunded mandate of Section 504 presents a challenge to K-12 public schools. A mixed methods design study was completed in schools in South Texas to access school administrative staff perceptions of strengths and challenges in Section 504-Only services and identify needed training and differences between elementary and secondary schools. Top concerns and needed training were identified. No statistical differences were found between elementary and secondary schools among the concerns. State and school administrators need to address concerns and provide needed training to school staff implementing Section 504 to support social justice in schools.